2003
DOI: 10.1063/1.1618018
|View full text |Cite
|
Sign up to set email alerts
|

Growth, branching, and kinking of molecular-beam epitaxial 〈110〉 GaAs nanowires

Abstract: GaAs nanowires were grown on GaAs (100) substrates by vapor–liquid–solid growth. About 8% of these nanowires grew in 〈110〉 directions with straight, Y-branched or L-shaped morphologies. The role of strain-induced reduction in surface free energy is discussed as a possible factor contributing to the evolution of 〈110〉 nanowires. Kinking and branching is attributed to growth instabilities resulting from equivalent surface free energies for 〈110〉 growth directions. Transmission electron microscopy verified that 〈… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
91
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 17 publications
3
91
0
1
Order By: Relevance
“…We note that multiple periodical twining is also observed at the initial stage of growth, frame number 1, which has already been reported before. [7][8][9] The FFTs of the nanowire and substrate indicate the same crystallographic orientation. The structure of the GaAs appearing at the nanocrater follows also the same orientation.…”
mentioning
confidence: 94%
“…We note that multiple periodical twining is also observed at the initial stage of growth, frame number 1, which has already been reported before. [7][8][9] The FFTs of the nanowire and substrate indicate the same crystallographic orientation. The structure of the GaAs appearing at the nanocrater follows also the same orientation.…”
mentioning
confidence: 94%
“…The end of these ZB wires invariably shows a kink in growth direction abruptly toward a particular h111i direction most likely (111)B. 22 There are shorter, narrower wires aligned with the h110i wafer edges that are growing completely in a h111i direction. No.…”
Section: Methodsmentioning
confidence: 99%
“…[7,8] In VLS growth of semiconductor NWs, several growth directions have been frequently observed, such as <111>, [2] <112>, [3,11,13] and <110>. [7,11,14,15] Recently, we have developed a method of synthesizing II-VI semiconductor NWs based on Au-catalyzed VLS using MBE. [11] We observed that ultrathin ZnSe (or ZnS) NWs grew epitaxially on GaP (111) substrates.…”
mentioning
confidence: 99%